Abdominal obesity and reduction of glomerular filtration - Dias,Raimunda Sheyla Carneiro (2018)
SUMMARY The objective was to evaluate the association between nutritional status and the glomerular filtration rate (GFR) in remaining quilombolas. Cross-sectional study carried out on 32 remaining quilombola communities in the municipality of Alcântara-MA. The nutritional indicators (IN) used were: body mass index (BMI); Waist circumference (WC); Waist-to-hip ratio (WHR); Waist-to-height ratio (WHtR); conicity index (CI) and estimated visceral adipose tissue (VAT). GFR was estimated from the CKD-EPI creatinine-cystatin C formula. The Shapiro Wilk test was used to evaluate the normality of the quantitative variables. In order to compare the second IN sex, the chi-square test was applied. The Anova or Kruskal-Wallis tests were used to verify the association between IN and GFR. Of the 1,526 remaining quilombolas studied, 89.5% were black or brown, 51.2% were women, 88.6% belonged to economic classes D and E and 61.2% were farmers or fishermen. Clinical investigation revealed 29.2% of hypertensive patients, 8.5% of diabetics and 3.1% with reduced GFR. The BMI revealed 45.6% of the remaining quilombolas with excess weight. When compared to men, women presented a higher prevalence of overweight by BMI (56.6% vs 33.8%, p <0.001) and abdominal obesity CC (52.3% vs 4.3%), WHR (76,5% vs 5.8%), WHtR (82.3% vs 48.9%) and VAT (27.1% vs 14.5%) (p <0.001). Comparing the means of IN according to the GFR, it was observed that the higher the mean value of the IN lower the GFR (p <0.05). The GFR reduced with increasing mean values of nutritional indicators of abdominal obesity, regardless of sex.